A Cohort Study of the Long-Term Influences of SARS-CoV-2 on Kidney Allograft Outcomes in Chinese Recipients: 1-Year Follow-Up Experience - Yisheng Ji; Shuang Fei; Hongsheng Ji; Fan OuYang; Runmin Ding; Li Sun; Hao Chen; Xiaobing Ju; Jun Tao; Zhijian Han; Mulong Du; Zijie Wang; et al. (Kidney Diseases)
Introduction: The aim of the study was to investigate the long-term effects of the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection and novel coronavirus disease (COVID-19) on prognosis of kidney transplant recipients. Methods: A 1-year retrospective study was carried out among 362 domestic kidney transplant recipients who were divided into observational (COVID-19) and control groups. Stratification analysis was then carried out to investigate whether repeated infections and infection severity could influence graft prognosis. Kaplan-Meier curves assessed 1-year graft survival, while one-way analysis of variance (ANOVA) compared graft function and laboratory parameters. Generalized estimating equations and repeated-measures ANOVA confirmed the magnitude of the impact of COVID-19 on kidney grafts. Generalized logistic regression and Cox regression established a model for analyzing COVID-19 risk factors. Meta-analysis and subgroup analysis were performed for validation. Results: Exposure of COVID-19 had a significant effect on graft function within 1 year (p < 0.001), and this kind of effect was mostly brought by severer infections in the stratification analysis regarding graft survival rate (p < 0.001), estimated glomerular filtration rate (eGFR) level (p < 0.001), and 1-year eGFR slope (p = 0.014). Diagnostic model showed tacrolimus patients are less likely to get severe COVID-19 than cyclosporine (p = 0.004). Hyperglycemia (p = 0.004) and low hemoglobin (p = 0.023) are adverse factors for severe pneumonia. Hemoptysis, hypo-lymphopenia, high procalcitonin and ferritin are linked to poor allograft outcomes with SARS-CoV-2 infection. Conclusions: COVID-19 severity is linked to poor kidney allograft prognosis. Hyperglycemia, low hemoglobin, and drug protocols including cyclosporine rather than tacrolimus are correlated with COVID-19 pneumonia. Hemoptysis, low lymphocytes, high procalcitonin or ferritin were concerned with kidney allograft prognosis post-COVID-19.